Pemanfaatan Teknologi Artificial Intelligence (AI) Untuk Mendukung Kualitas Pendidikan di SMA Negeri 1 Kalibawang - Murti Retnowo; Agus Suhendar; Sutarman; Farida Ardiani (Jurnal ABDI RAKYAT, 2024)
Artificial intelligence technology offers various benefits for teaching staff, which can improve the quality of teaching and the efficiency of the educational process. Artificial intelligence technology makes it very easy for teachers to prepare materials, learning methods and case studies that are relevant to the subjects taught by the teacher. An obstacle that often occurs and is faced by teachers is when teachers prepare material and deliver material using artificial intelligence (AI) technology, so it is felt necessary to hold training on the use of artificial intelligence technology, especially for teaching teachers. Through mentoring to increase teacher competency, it is hoped that teachers can be more creative and more innovative in preparing and delivering material to students. Teachers are also expected to be able to provide examples that are appropriate to the subjects taught and adapt to the current age development of students. Learning by utilizing AI technology is also expected to be able to reduce students' dependence on social media or online games which are often played by students, apart from that students are also required to read more to increase their insight in the teaching and learning process